Establishing a core outcome set for creatine transporter deficiency and guanidinoacetate methyltransferase deficiency - Nasseri Moghaddam, Zahra; Reinhardt, Emily K.; Thurm, Audrey; Potter, Beth K.; Smith, Maureen; Graham, Celeste; Tiller, Beth H.; Baker, Steven A.; Bilder, Deborah A.; Bogar, Regina; Britz, Jacobus; Cafferty, Rachel; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Creatine transporter (CTD) and guanidinoacetate methyltransferase (GAMT) deficiencies are rare inborn errors of creatine metabolism, resulting in cerebral creatine deficiency. Patients with either condition commonly exhibit intellectual and developmental disabilities, often accompanied by behavior problems, delayed speech, seizures, and motor impairments. There is currently no efficacious treatment for CTD, while current management for GAMT requires lifelong treatment with a protein restricted diet and intake of high amounts of oral supplements. Efforts to conduct clinical trials on potential treatments for these disorders are made more difficult by the lack of clinical and patient-derived meaningful outcomes. A core outcome set (COS) can facilitate consistent use of outcomes in studies. The current effort included patient and caregiver perspectives into the outcome selection of a COS for CTD and GAMT. Results We partnered with caregivers and health professionals to establish the first COS for CTD and GAMT. The COS developed includes seven outcomes (“Adaptive Functioning”, “Cognitive Functioning”, “Emotional Dysregulation”, “MRS Brain Creatine”, “Seizure/Convulsions”, “Expressive Communication”, and “Fine Motor Functions”) for both CTD and GAMT, and an additional outcome for GAMT (“Serum/Plasma Guanidinoacetate”) that are important to stakeholders and consequently should be considered for measurement in every clinical trial. Caregivers were valued partners throughout the COS development process, which increased community engagement and facilitated caregiver empowerment. Conclusions Development of this COS illustrates a patient-centered approach for clinical trial readiness for CTD and GAMT that if utilized will make clinical trial results comparable, minimize bias in clinical trial outcome selection, and promote efficient use of resources.